Active Layer and Permafrost Investigations Using Geophysical and Geocryological Methods—A Case Study of the Khanovey Area, Near Vorkuta, in the NE European Russian Arctic - Rossi, Mara; Dal Cin, Michela; Picotti, Stefano; Gei, Davide; Isaev, Vladislav S.; Pogorelov, Andrey V.; Gorshkov, Eugene I.; Sergeev, Dmitrii O.; Kotov, Pavel I.; Giorgi, Massimo; Rainone, Mario L. (Frontiers in Earth Science, 2022)
Permafrost in the NE European Russian Arctic is suffering for some of the highest degradation rates in the world. The rising mean annual air temperature causes warming permafrost, the increasing of the Active-Layer Thickness (ALT), and the reduction of the permafrost extent. These phenomena represent a serious risk for infrastructures and human activities. ALT characterization is important to estimate the degree of permafrost degradation. We use a multidisciplinary approach to investigate the ALT distribution in the Khanovey railway station area (close to Vorkuta, Arctic Russia), where thaw subsidence leads to railroad vertical deformations up to 2.5 cm/year. Geocryological surveys including vegetation analysis and underground temperature measurements, together with the faster and less invasive Electrical Resistivity Tomography (ERT) geophysical method, are used to investigate the frozen/unfrozen ground setting between the railroad and the Vorkuta River. Borehole stratigraphy and landscape microzonation indicate a massive prevalence of clay and silty clay sediments at shallow depths in this area. The Complex Refractive Index Method (CRIM) is used to integrate and quantitatively validate the results. The data analysis shows landscape heterogeneity and maximum ALT and permafrost thickness values of about 7 m and 50 m, respectively. The active layer is characterized by resistivity values ranging from about 30 Ωm to 100 Ωm, while the underlying permafrost resistivity exceeds 200 Ωm, up to a maximum of about 10 KΩm. In the active layer there is a coexistence of frozen and unfrozen unconsolidated sediments, where the ice content estimated using CRIM ranges from about 0.3-0.4 to 0.9. Moreover, the transition zone between the active layer base and the permafrost table, whose resistivity values range from 100 Ωm to 200 Ωm for this kind of sediments, shows ice contents ranging from 0.9 to 1.0. Taliks are present in some depressions of the study area, characterized by minimum resistivity values lower than 10 Ωm. This thermokarst activity is more active close to the railroad, because of the absence of insulating vegetation. This study contributes to a better understanding of spatial variability of cryological conditions and the result is helpful to address engineering solutions for the stability of the railway.